A Multidisciplinary Team Approach to the Management of Patients with Hepatocellular Carcinoma with Portal Vein Tumor Thrombus. (6th March 2020) - Cheng, Shuqun; Wei, Xubiao; Shi, Jie; Guo, Weixing; Feng, Shuang; Zhai, Jian; Huang, Bin
Abstract : Treatment of patients with hepatocellular carcinoma and portal vein tumor thrombus is complex and requires a multidisciplinary team. This letter describes a multidisciplinary diagnosis and treatment center that was established to provide the most effective therapies for these patients, briefly reporting the resulting improvements in patient management.